Native reverberation: artistic acoustics for the outdoor stage on the Castle Creek campus - Banks, Robin (Kansas State University, 2009)
This project addresses landscape acoustics for a complex site and complex program. The site is a campus owned by two separate yet equally important entities, the Aspen Music Festival and School and the Aspen Country Day School. Each owner has very different program requirements for the Campus. Because of a mountainous setting the Campus is surrounded by natural hazards affecting the development potential of the site. Most importantly, the program requires performance and practice spaces for the music students. These spaces should be acoustically sound. However, acoustics in the outdoors is rarely thought of in the design profession. More often, sound is considered strictly in the sense of noise control. Carefully placing and designing the outdoor spaces for the students will enhance the acoustic quality, environmental sensitivity and unity of the campus as a significant and unique place. To enhance the acoustical experience of the Castle Creek Campus this research addresses what characteristics affect the movement of sound. This research identifies which outdoor environments propagate or hinder sound movement. A comparative sound study first identifies, locates and records characteristics of the campus. Some of these characteristics include the height of tree canopy, amount of enclosure, and surface type, for example. The audio recordings of the characteristics are then analyzed quantitatively and qualitatively, and ranked accordingly. This method allows for replicable results in other geographical areas. The ranking system results show that the appropriate location for the primary performance space is near calm water with little obstruction on three sides. The location for the practice spaces is generally, most appropriate in heavily wooded areas with dense canopy coverage. The results of the research guide the location and design of the required outdoor performance and practice spaces for the Castle Creek Campus serves as an example for incorporating acoustics into design.
Keywords: acoustic; landscape; Landscape Architecture (0390)